2014
DOI: 10.18632/oncotarget.1825
|View full text |Cite
|
Sign up to set email alerts
|

miR-34: from bench to bedside

Abstract: The mir-34 family was originally cloned and characterized in 2007 as a p53 target gene. Almost immediately it became clear that its major role is as a master regulator of tumor suppression. Indeed, when overexpressed, it directly and indirectly represses several oncogenes, resulting in an increase of cancer cell death (including cancer stem cells), and in an inhibition of metastasis. Moreover, its expression is deregulated in several human cancers. In 2013, a miR-34 mimic has become the first microRNA to reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
214
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(222 citation statements)
references
References 97 publications
4
214
0
2
Order By: Relevance
“…This is in accordance with current literature: the miR-34 family (miR-34a, b, and c) is attracting a lot of attention since it has been found to play a key role as a tumor suppressor in several cancers. 29 Indeed, it is a direct target of the tumor-suppressor gene p53 inducing apoptosis, cell cycle arrest, and senescence when upregulated. It also negatively influences the viability of cancer stem cells and inhibits metastasis formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with current literature: the miR-34 family (miR-34a, b, and c) is attracting a lot of attention since it has been found to play a key role as a tumor suppressor in several cancers. 29 Indeed, it is a direct target of the tumor-suppressor gene p53 inducing apoptosis, cell cycle arrest, and senescence when upregulated. It also negatively influences the viability of cancer stem cells and inhibits metastasis formation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the miR-34 family members bind to the 3ʹ-UTRs of genes such as CDK4 and CDK6 (cell cycle proteins), Bcl-2 (an apoptosis regulator), SNAIL (epithelial-mesenchymal transition) and CD44 (migration and metastasis), thus repressing their expression. 29 Numerous studies have shown the dysregulation of miR-34 in various types of cancers, including hepatocellular, mesothelial and colon cancer, melanomas, leukemia, nasopharyngeal cancer, 30 prostate cancer, 31 neuroblastomas, 32 glioblastoma 33 and breast cancer. 34 Yet, little research has been conducted in EC, apart from a functional study by Li et al 35 demonstrating that miR-34c acts as a tumor suppressor in HEC-1-B cells, and that E2F3 protein may be a target of miR-34c.…”
Section: Discussionmentioning
confidence: 99%
“…More impressively, MRX34, a liposome-based miR-34 mimetic developed by Mirna Therapeutics, has entered the phase of clinical trials for treating patients with liver cancer. The tumor suppressor miR-34a down regulates a number of key oncogenes, including MET, MEK1, CDK4/6, NOTCH, CD44, and immune evasion gene PDL1 [87]. The update on clinical trial with MRX34 American Society of Clinical Oncology (ASCO) Annual meeting 2016 reported that MRX34 has a manageable toxicity profile and evidence of activity in liver cancer, renal cell carcinoma, and melanoma during the phase I study (Hong et al oral presentation at ASCO annual meeting 2016, abstract # 2508).…”
Section: Potential Use Of Microrna For Cancer Therapeuticsmentioning
confidence: 99%
“…Studies have shown that miR-34 family members regulate cell proliferation, cell migration, and apoptosis by functioning downstream of p53 signaling (Wang et al, 2013;Agostini and Knight, 2014). For example, miR-34c is functionally required for spermatogenesis (Massimiliano et al, 2011;Liu et al, 2012), whereas miR-34a is involved in neuronal development.…”
Section: Northern Blot Analysismentioning
confidence: 99%